Validity of Selling Plants of Land with Credit in The Prespective of National Agrarian Law - Suyanto; Mokh Thoif; Subekti (LEGAL BRIEF, 2022)
In meeting the personal and social needs of the community for land in everyday life and with limited purchasing power in the midst of an economic downturn due to the Covid-19 pandemic and limited availability of residential land, for land sellers it is carried out by providing land through plots of land in the form of plots -Plots are ready to build while for buyers it is done by installment or credit. This research is a normative research that examines various laws and regulations, norms, concepts and jurisprudence using a conceptual, statutory and philosophical approach. In making a sale and purchase agreement Land sale and purchase agreements are generally subject to articles 1457, 1458 and 1459 Burgelijk wet Boek (BW), which require a seller and a buyer and the legal terms of the agreement as stipulated in article 1320 BW, which are marked by an agreement and the surrender of the object (levering) but since the enactment of the Basic Agrarian Law the provisions for buying and selling land are subject to customary law, namely carried out with the cash and clear concept.